Frequent promoter hypermethylation and expression reduction of the glucocorticoid receptor gene in breast tumors - Nesset, Kirsten A (Landes Bioscience, 2014)
Previous studies have found that expression of the Glucocorticoid Receptor (GR) is altered or reduced in various cancers, while the GR promoter has been shown to be methylated in gastric, lung, and colorectal cancers. Examining a small cohort of matched normal and breast cancer samples we found that GR levels were dramatically reduced in almost all tumors in relation to their normal tissue. The methylation status of the GR promoter was assessed to determine if this observed decrease of expression in breast tumors could be due to epigenetic regulation. While it was not methylated in normal tissue, the GR proximal promoter was methylated in 15% of tumor samples, particularly, but not exclusively, in Estrogen Receptor positive tumors. GR expression in these tumors was particularly low and loss of GR expression was specifically correlated with methylation of the proximal promoter GR B region. Overall, these results show that hypermethylation of the promoter in tumors is a frequent event and suggests that GR may act as a tumor suppressor in breast tissue.